Thermal Noise‐Induced Phase Transition in Multi‐Domain Hf‐Based Antiferroelectric Material: Fatigue and Endurance Performance - Sheng Luo; Zijie Zheng; Zuopu Zhou; Xiao Gong; Gengchiau Liang (Advanced Electronic Materials)
Abstract The deterioration of the endurance performance in the Hf‐based antiferroelectric (AFE) material is a crucial challenge in the reliability of its device applications, and it is important to identify the mechanism for further optimizations. In this work, a stochastic AFE dynamic model is proposed to characterize the fatigue behaviors induced by thermal noise‐induced lattice vibration. Through the analysis of the noise‐assisted phase transition between the antiferroelectric and ferroelectric (FE) phases, the impact of the thermal effect on endurance is evaluated and the results are in good agreement with the experiments. Both temperature and dipole coupling strength are found to be the key factors in noise‐induced fatigue. Furthermore, the thermal noise‐induced stochastic dynamics is found to have a profound impact in the AFE‐based memory's reliability, and the memory window demonstrates direct dependency on temperature and domain dynamics.